Fast retention of isoniazid on organobentonite prepared using green chemistry approach: contribution of the pi interactions - ÇALIŞKAN SALİHİ, ELİF (TAYLOR & FRANCIS INC, 2019)
In the present study, a new organoclay adsorbent for the adsorption of isoniazid (INH) was produced with the modification of bentonite using green chemistry approach. Glycine was used for the modification because of being environmentally friendly and biocompatible. Then the removal of INH was studied in aqueous solutions. Experiments were conducted as a function of contact time, initial concentration and solution pH to understand the adsorption mechanism. The equilibrium time for the adsorption was found as 20 min. Adsorption capacity of the adsorbent was increased from 21.10 mg/g to 33.90 mg/g after modification. The maximum adsorption was observed at pH 1.5. The results showed that INH was physisorbed on the adsorbents with the contribution of pi dispersion interactions.
Keywords: Adsorption; organobentonite; glycine; dispersion interactions; antibiotics; PERSONAL CARE PRODUCTS; PHARMACEUTICALLY ACTIVE COMPOUNDS; AQUEOUS-SOLUTIONS; WASTE-WATER; AQUATIC ENVIRONMENT; SURFACE-CHEMISTRY; RISK-ASSESSMENT; ADSORPTION; REMOVAL; MONTMORILLONITE